72.9k views
5 votes
PLEASE HELP ASAP I NEED HELP WILL GIVE EXTRA POINT Given that f(x) = x^2+3x -5 and g(x)= x +4 find g(f(x)) when x = 1

User Mike Hardy
by
5.8k points

2 Answers

3 votes


\bf \begin{cases} f(x)=x^2+3x-5\\ g(x)=x+4 \end{cases} \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ \stackrel{x=1}{f(1)}=(1)^2+3(1)-5\implies \boxed{f(1)}=-1 \\\\[-0.35em] ~\dotfill\\\\ g(~~f(x)~~)=[f(x)]+4\implies g(~~f(1)~~)=[f(1)]+4 \\\\\\ g(~~f(1)~~)=\boxed{-1}+4\implies \blacktriangleright g(~~f(1)~~)=3 \blacktriangleleft

User Matheus Torquato
by
5.5k points
4 votes
I think the answer is 3. Plug in the value of x (1) into the f(x). Then solve to find that f(x)= -1, then plug in -1 to x in g(x) to get that g(f(x))=3
User Rettichschnidi
by
5.7k points